Filmes de nanocristais e nanofibrilas de celulose de eucalipto e abacaxi (curauá) por continous casting - Claro, Pedro Ivo Cunha (Universidade Federal de São Carlos, 2017)
New materials from cellulose have been developed, such as cellulose nanocrystals (CNC) and cellulose nanofibrils (CNF). Different morphologies of the cellulose can lead to the formation of films with different thermal, mechanical and optical properties in relation to conventional cellulose films. The objective of this work was to evaluate the effect of different dimensional scales of cellulose, micro and nanometric, on the production of cellulose films from two vegetable species and their thermal, mechanical, morphological and optical properties. Eucalyptus fibers and pineapple leave fiber (curauá) (PALF) were used as cellulosic fibers for this study. The films of eucalyptus and pineapple cellulosic fibers were prepared by filtration and casting, and the CNC and CNF films were obtained by continuous casting. The CNC and CNF films showed mechanical tensile strength in the order of 9 to 35 MPa higher than the films of cellulose fibers, regardless of the origin of the fiber. The continuous casting process produced CNC and CNF films that presented different mechanical resistance in the longitudinal direction of the process with respect to the transverse direction. This behavior may be related to how hydrogen bonds and mechanical anchorages occur between nanofibers. The thermal stability of the nanocellulose films was lower in the order of 20 to 150 ºC than in the films of fibers due to the routes of obtaining the CNC and CNF. Nanofiber films presented lower opacity in the order of 3 to 60% lower than the films of fibers due to the diameter of the nanocelluloses. Curauá fibers had the highest crystallinity index (Ic) reaching 87%. It is concluded that the properties studied were influenced by the type of nanocellulose (CNC or CNF), the origin of the cellulose (eucalyptus or pineapple), and the micro and nanometric scale of the fibers.
Cellulose nanocrystals and nanofibrils films of eucalyptus and pineapple (curauá) by continuing casting
Keywords: Eucalipto; Abacaxi; Filme; Nanocristais de celulose; Nanofibrilas de celulose; Continuous casting; Eucalyptus; Pineapple; Films; Cellulose nanocrystals; Cellulose nanofibrils; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA